Genotype-phenotype analysis of hearing function in patients with DFNB1A caused by the c.-23+1G>A splice site variant of the GJB2 gene (Cx26). - Fedor M Teryutin; Vera G Pshennikova; Aisen V Solovyev; Georgii P Romanov; Sardana A Fedorova; Nikolay A Barashkov (PLoS ONE)
The audiological features of hearing loss (HL) in patients with autosomal recessive deafness type 1A (DFNB1A) caused by splice site variants of the GJB2 gene are less studied than those of patients with other variants of this gene. In this study, we present the audiological features of DFNB1A in a large cohort of 134 patients with the homozygous splice site variant c.-23+1G>A and 34 patients with other biallelic GJB2 genotypes (n = 168 patients with DFNB1A). We found that the preservation of hearing thresholds in the speech frequency range (PTA0.5,1.0,2.0,4.0 kHz) in patients with the c.[-23+1G>A];[-23+1G>A] genotype is significantly better than in patients with the "severe" c.[35delG];[35delG] genotype (p = 0.005) and significantly worse than in patients with the "mild" c.[109G>A];[109G>A] genotype (p = 0.041). This finding indicates a "medium" pathological effect of this splice site variant on hearing function. A detailed clinical and audiological analysis showed that in patients with the c.[-23+1G>A];[-23+1G>A] genotype, HL is characterized as congenital or early onset (57.5% onset before 12 months), sensorineural (97.8%), bilateral, symmetrical (82.8%), variable in severity (from mild to profound HL, median hearing threshold in PTA0.5,1.0,2.0,4.0 kHz is 86.73±21.98 dB), with an extremely "flat" audioprofile, and with a tendency toward slow progression (a positive correlation of hearing thresholds with age, r = 0.144, p = 0.041). In addition, we found that the hearing thresholds in PTA0.5,1.0,2.0,4.0 kHz were significantly better preserved in females (82.34 dB) than in males (90.62 dB) (p = 0.001). We can conclude that in patients with DFNB1A caused by the c.-23+1G>A variant, male sex is associated with deteriorating auditory function; in contrast, female sex is a protective factor.